A generic competency framework for entry level construction managers in Malaysia / Haryanti Mohd Affandi - Mohd Affandi, Haryanti (Institute of Graduate Studies, UiTM, 2015)
The changes in industry needs have further highlighted the problems of incompetence entry level construction managers and brought significant changes in construction management education. Moreover, culmination from the issues faced in the entry level construction management, it suggests that there is problem relating to the mismatch of generic competency in entry level construction management. The mismatch of generic competency appears when there are changes in industry requirements added with education provision in developing construction management students’ generic competency. Furthermore, there’s an absence of strategic framework for Malaysian entry level construction managers. The aim of this research is to address part of the problem in construction management generic competency education and construction industry by suggesting an improved generic competency framework of entry level construction managers in Malaysia. This study adopts a mixed method approaches and results from questionnaire survey and interviews which highlight the major issues. Sequential explanatory model are chosen in determining the mismatch. In developing the generic competency framework, this study adapts and improves Spencer & Spencer (1993) competency development model…